KCNH3 Predicts Poor Prognosis and Promotes Progression in Ovarian Cancer - Li Z (OncoTargets and Therapy, 2020)
Zhongjun Li,1,2,* Lishan Huang,1,* Li Wei,1 Bin Zhang,1 Shulin Zhong,1 Yijing Ou,1 Chuangyu Wen,1 Suran Huang1 1Department of Obstetrics and Gynecology, Affiliated Dongguan People’s Hospital, Southern Medical University, Dongguan, Guangdong, 523059, China; 2Department of Obstetrics and Gynecology, Nanfang Hospital, Southern Medical University, Guangzhou, Guangdong, 510515, China*These authors contributed equally to this workCorrespondence: Chuangyu Wen; Suran HuangDepartment of Obstetrics and Gynecology, Affiliated Dongguan People’s Hospital, Southern Medical University, 3 Wangdao Road, Dongguan, Guangdong 523059, ChinaEmail wenchy5@mail.sysu.edu.cn; suranhuangdg@163.comBackground: Ovarian cancer (OC) is one of the most common causes of cancer-related death among women; accordingly, new biomarkers of OC are urgently needed. Potassium voltage-gated channel sub-family H member 3 (KCNH3) is a voltage-gated potassium channel member involved in cognitive function and diabetes. Here, we aimed to elucidate the role and potential molecular mechanisms of KCNH3 in OC.Materials and Methods: KCNH3 expression levels in OC tissues were analyzed using TCGA data and confirmed by RT-qPCR and immunohistochemistry in OC tissues. The cell counting kit-8 was used to assess cell proliferation in OC cells in which KCNH3 was knocked-down with small interference RNA (siRNA). Wound-healing and transwell invasion assays were used to assess migratory and invasive abilities, respectively. Cell cycle distribution and apoptosis were determined using a flow cytometer. Gene set enrichment analysis and Western blot were used to investigate the potential pathways of KCNH3 in OC development.Results: TCGA data and RT-qPCR results from patients with OC revealed high KCNH3 expression in OC tissues compared to normal ovarian tissues. Survival analysis in patients with OC suggested that high KCNH3 expression might be an independent predictor for poor overall survival and disease-free survival. In vitro studies showed that KCNH3 silencing in OC cells could inhibit cell proliferation and migration ability, and induce apoptosis and G2/M phase arrest. Furthermore, Western blot results showed that KCNH3 silencing might induce downregulation of RPA1 and RPA2 expression level in both SKOV3 and COC1 cells.Conclusion: KCNH3 plays an important role in cancer progression in patients with OC. Further investigation might reveal KCNH3 as a potential biomarker for prognosis or diagnosis in OC.Keywords: KCNH3, ovarian cancer, prognosis, replication protein A